KONSEP MUHAMMAD SHAHRU TENTANG AURAT PEREMPUAN - Laila Nurul hidayah (LP2M Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2020)
In Islam, clothing does not only function as jewelry and body armor from heat and cold, but more importantly is to cover the nakedness. Al-Qur'an al-Karim shows the obligation of women to cover their bodies in His words,